Healthy Food Access and Affordability: “We Can Pay the Farmer or We Can Pay the Hospital" - Schumacher, Gus; Nischan, Michel; Simon, Daniel (Maine Policy Review, 2011)
The authors provide a history and overview of Federal food assistance efforts, especially food supplement programs, and the policy implications for Maine and national nutrition-incentive programs. They present a profile of the work of Wholesome Wave which aims to increase affordability and access to locally-grown food.
Keywords: food access; food stamps; SNAP; Wholesome Wave; Maine; food policy